2014
DOI: 10.5897/ijbc2013.0597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physico-chemical conditions on the structure and composition of the phytoplankton community in Wular Lake at Lankrishipora, Kashmir

Abstract: The high altitude valley of Kashmir abounds in a vast array of freshwater bodies of lotic as well as lentic nature. Amongst these, lakes play an important role in biodiversity of this region. The present study on Wular Lake, Kashmir was undertaken from March, 2007 to February, 2008 to study abundance and distribution of phytoplankton and their correlation with physico-chemical conditions of water. A total of 64 phytoplankton belonging to bacillariophyceae, chlorophyceae, cyanophyceae and euglenophyceae were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 6 publications
(5 reference statements)
2
9
1
Order By: Relevance
“…In the present study, Microcystis was also recorded in the selected site table 2. The occurrence of Oscillatoria in the present study indicates pollutants of biological origin which agreed with the observations of Altaf and Saltanat (2014) and Gadag et al (2005).…”
Section: Resultssupporting
confidence: 82%
“…In the present study, Microcystis was also recorded in the selected site table 2. The occurrence of Oscillatoria in the present study indicates pollutants of biological origin which agreed with the observations of Altaf and Saltanat (2014) and Gadag et al (2005).…”
Section: Resultssupporting
confidence: 82%
“…This study agreed with reports of diatom diversity and distribution in shallow lakes of Wapusk National Park (Manitoba, Canada) it shows that the most abundant taxa of the above lake are Nitzschia which is not common in other Eco zones by Jacques O, et al [26]. Therefore, the current findings are similar with that of Altaf H, et al & Ganai AH, et al [25,27]. In the second study period the Bacillariophyta, Cyanophyta, Chlorophyta and Euglinophyta were dominant identified genera in Lake Abaya Siltie Zone.…”
Section: Discussionsupporting
confidence: 93%
“…From phylum Bacillariophyta /diatom group is second dominant phylum during the first study period and among the identified genera of Bacillariophyta highly dominant genera were Nitzschia and Melisora respectively 67.17 % and 29.57%. As investigate that Bacillariophyta remained dominant in the lake during winter because of they are able to grow under the condition of weak light and low temperature which are less suitable for other algae and low concentration of nutrients (NO3-N AND PO4-P) in the winter [25]. This study agreed with reports of diatom diversity and distribution in shallow lakes of Wapusk National Park (Manitoba, Canada) it shows that the most abundant taxa of the above lake are Nitzschia which is not common in other Eco zones by Jacques O, et al [26].…”
Section: Discussionmentioning
confidence: 99%
“…A sizeable fraction of the published works with incomplete species inventories and inadequate data-analysis comprise 'routine' ecology reports (Sharma, 2015). The noteworthy phytoplankton diversity Indian studies relate to the lakes of Kashmir (Zutshi et al, 1980;Zutshi and Wanganeo, 1984;Wanganeo and Wanganeo, 1991;Baba and Pandit, 2014;Ganai and Parveen, 2014), Himachal Pradesh (Thakur et al, 2013;Gupta et al, 2018;Jindal et al, 2013Jindal et al, , 2014aJindal et al, , 2014b and Uttarakhand (Sharma and Singh, 2018;Sharma and Tiwari, 2018;Singh and Sharma, 2018). Certain notable works from NEI are from the floodplain lakes (beels) of the Brahmaputra river basin of Assam (Sharma, 2004(Sharma, , 2012(Sharma, , 2015Sharma and Hatimuria, 2017) and pats of the floodplains of Manipur (Sharma, 2009(Sharma, , 2010.…”
Section: Introductionmentioning
confidence: 99%